The perfect storm of business venturing? The case of entomology-based venture creation - Stefano Pascucci; Domenico Dentoni; Dimitrios Mitsopoulos (Agricultural and Food Economics, 2015)
In this paper we discuss how cooperation and trust among entrepreneurs can be challenged when they are dealing with venture creation in the context of radical innovation. Entomology-based foods are considered as one of the most promising innovation in the food sector. However they impose radical changes in food consumption habits with high risk of low consumer acceptance. Four European entrepreneurs joined forces in a new venture operating in this sector, trying to make it a successful business. We asked two of them to participate in a venture creation game experiment. The results indicate that high individualized pay-offs can lead the entrepreneurs to deviate from trust and cooperation.
Keywords: 330; Venture creation; Radical innovation; Insects; Prisoner's Dilemma